Coherence and wavelength effects on the growth mechanism of porous silicon nano-structures - Saygılı, Aslı Çakır. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
In this study, the objective is first to produce regular porous silicon(PS) nanostructures and then to observe the effects of wavelength and coherence length of the light, which is used for illumination, on the growth mechanism of these structures. P+ type silicon wafers are exposed to various light sources, both coherent and incoherent. Lasers with different wavelengths are used to compare the wavelength effects and light emitting diode is employed to compare the effects of coherence lenght on the porous silicon’s growth mechanism. The nanocrystalline silicon samples formed in the electrochemical dissolution are characterized in terms of optics and structure. An optical characterization method is used to analyze the origin of nanocrystal silicon luminescence and radiative recombination mechanism. Optical characterization is also capable to show if the porous nano-structures are formed or not. Optical results are supported by structural characterization methods; such as AFM (Atomic Force Microscope) and ESEM (Environmental Scanning Electron Microscope). In these methods, images, taken from each sample at different magnifications, denote characteristics of formed pores such as size and shape.
Keywords: Nanosilicon.; Porous silicon.; Luminescence.